The predictive validity of the V-RISK-10 and BVC among involuntarily admitted patients - Kös, Tilmann; Bräunig, Peter; Hausam, Joscha (Frontiers in Psychiatry, 2024)
Although endangerment towards others is a criterion for an involuntary admission in many countries, research on risk assessment of endangerment among involuntarily admitted individuals is limited. In this retrospective case-control study, we calculated scores for a German-translated version of the Violence Risk Screening-10 (V-RISK-10) and the Brøset Violence Checklist (BVC) in a sample of 111 people undergoing an involuntary admission in Reinickendorf, Berlin. Outcomes were violence, coercive measures, and readmission. In line with our hypotheses, the BVC demonstrated stronger predictive validities for short-term, and V-RISK-10 for long-term events. There was an incremental validity for both instruments for restraint 24 hours after admission and any violence until discharge. These findings support the evidence that structured risk assessment instruments may be useful for individuals undergoing an involuntary admission. Ethical considerations about screening procedures are discussed.